2010
DOI: 10.1117/1.3497051
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the modulation transfer function of an imaging spectrometer with rooflines of opportunity

Abstract: Measuring the modulation transfer function (MTF) of digital imagers focused at or near infinity in laboratory or field settings presents difficulties because the optical path is longer than a typical laboratory. Also, digital imagers can be hindered by low-resolution detectors, resulting in the resolution of the optics surpassing that of the detector. We measure the MTF for a short-wave infrared hyperspectral imager developed by Resonon, Inc., of Bozeman, Montana, which exhibits both characteristics. These dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…These two approaches are generally referred to as the diffractive MTF and the geometric MTF respectively [4]. Any MTF quantifies the system's capacity to spatially resolve a sinusoidal intensity pattern with discernible contrast [4,7]. Previous studies have proposed several methods for measuring the MTF of optical systems based on detector arrays of charge-coupled devices (CCDs) [8] and most of them differ essentially in the type of target or pattern used as the object pattern [9].…”
Section: Introductionmentioning
confidence: 99%
“…These two approaches are generally referred to as the diffractive MTF and the geometric MTF respectively [4]. Any MTF quantifies the system's capacity to spatially resolve a sinusoidal intensity pattern with discernible contrast [4,7]. Previous studies have proposed several methods for measuring the MTF of optical systems based on detector arrays of charge-coupled devices (CCDs) [8] and most of them differ essentially in the type of target or pattern used as the object pattern [9].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the aliasing effect, the knife-edge is tilted slightly and the construction of the oversampled ESF is realised at the subpixel spacing [14]. Experimentation showed that a subpixel bin of one-quarter pixel had the best results [15]. Recently virtual knife edge has been proposed by Karcher et al [16].…”
Section: B Overview Of the Measurement Techniquesmentioning
confidence: 99%
“…10562 105623D-4 The tilted edge was used to construct a superresolution 1-D ESF, which was resampled at quarter-pixel increments to provide data with four times the resolution of the detector. Image courtesy [15] We notice that the estimation of the PRF through the ESF must be done carefully to avoid bias in the result as the intensity profile (erf function) or its derivative (Gaussian function) are very sensitive to noise. Among all these techniques, the spot scan is the most effective for the investigation of the intrapixel sensitivity analysis.…”
Section: B Overview Of the Measurement Techniquesmentioning
confidence: 99%
“…According to different signal patterns, three common methods can be used to estimate the absolute MTF: step edge method [1], point source method [2], and rectangular pulse method [3]. Since the step edges are easy to find in practice, the step edge method is the most widely adopted one.…”
Section: Introductionmentioning
confidence: 99%